Features of braking of multi-axle vehicles depending on the layout of their axles - Bogomolov, V. O.; Klimenko, V. I.; Leontiev, D. M.; Frolov, A. A.; Suhomlin, O. S.; Kuripka, O. V.; Богомолов, В. О.; Клименко, В. І.; Леонтьєв, Д. М.; Фролов, А. А.; Сухомлин, О. В.; Куріпка, О. В. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. For an hour, in the scientific-methodical recommendations of the ship-experts, it is installed in the scientific-technical literature of the day-to-day parameters of galvanizing of vantage, bug-capable transport equipment, so that it is inaccurate to introduce autotransport equipment for the eastern part to inaccurate zasob_v unique road transport suit. Goal. The value of the function of galvanizing large transport bridges on the basis of the coordinates of the position to the center of the heavy transport, realizable values, which are realized between the tires and the supporting surface, as well as the support for the rear axle of the transport bridges. Methodology. The approaches adopted in the work to solve this goal are based on the theoretical foundations of braking multi-axle vehicles, the scientific provisions of elastic defor-mations of pneumatic tires of automobile wheels, geometric and weight parameters of a wheeled vehicle. Results. The equations that allow to calculate the value of the braking coefficient of multi-axle vehicles based on the coordinates of the position of the center of gravity, the realized couplings between the tires and the bearing surface, as well as the load distribution between the respective front and rear axles of the vehicle. Rivnyannya is assigned, which allow the positioning of the coordinates to the center of the car of a multi-axle wheeled transport vehicle for both front and rear axles. The calculation schemes of the position of the coordinates of the center of mass for two-axle, three-axle and four-axle with different axle layout are presented in graphical form, which give a general idea of the mass distribution between the front and rear axles of the vehicle. Originality. Presented in a graphical view of the layout of the positioning of the coordinates to the center of the car for a two-axle, three-axle and one axle with a small layout of the bridges, which give a far-reaching display of the space between the front and rear axles of the transport vehicle. Practical value. The results can be recommended by the experts-auto technicians in the development of technical capabilities for the drivers of vantage transport means, uniqueness of the road-transport usability.
Особливості гальмування багатовісних транспортних засобів в залежності від компановки їх мостів
Keywords: multi-axle vehicle; wheeled vehicle; braking rate; pneumatic tire; interaction with the road surface; braking parameters; багатовісний транспортний засіб; колісний транспортний засіб; коефіцієнт гальмування; пневматична шина; взаємодія з поверхнею дорожнього покриття; параметри гальмування; 629.3.017.5; 10.30977/AT.2019-8342.2021.49.0.04